God's action in nature's world: essays in honour of Robert John Russell - Peters, Ted; Hallanger, Nathan; Russell, Robert J.; Russell, Robert J. (Ashgate science and religion series, 2006)
Robert John Russell's contribution to the theology & science dialogue / Ted Peters -- Relating the natural sciences to theology : levels of creative mutual interaction / William R. Stoeger -- Creative mutual interaction : Robert John Russell's contribution to theology and science methodology / Nancey Murphy -- 'Creative mutual interaction' as manifesto, research program, and regulative ideal / Philip Clayton -- 'Creative mutual interaction' as an epistemic tool for interdisciplinary dialogue / J. Wentzel van Huyssteen -- The sciences and the religions : some preliminary East Asian reflections on Christian theology of nature / Heup Young Kim -- Atoms may be small, but they're everywhere : Robert Russell's theological engagement with the quantum revolution / Kirk Wegter-McNelly -- Indeterminacy, holism, and God's action / Ian G. Barbour -- Basic puzzles in science and religion / Charles H. Townes -- Quantum theology / John Polkinghorne -- Robert John Russell's theology of God's action / Wesley J. Wildman -- Today's playing field : theology and science / George V. Coyne -- Emergent realities with causal efficacy : some philosophical and theological applications / Arthur Peacocke -- Noninterventionist divine action : Robert Russell, Wolfhart Pannenberg, and the freedom of the (natural) world / Lou Ann Trost -- How many universes? / Paul Davies -- Bodies matter : a new fad and a fallacy in the name of science / Noreen Herzfeld